The Effectiveness of Smart Learning Based on Expert Systems in Cryptography Courses - Mochammad Iswan; M. Syaifuddin; Rian Farta Wijaya (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
The development of science and technology requires universities not only to matter but also to have abilities in their respective fields including Security System. The unavailability of network design laboratory and its minimum, network design, cryptography design and flexibility of face-to-face time in the discussion of material compiled not in accordance with the competencies in this course. To overcome these deficiencies in learning activities, development of a project-based blended learning model is carried out. The development carried out in this study uses the Puslitjaknov development model which reduces the Borg and Gall stages to five stages namely product analysis, initial product design, expert validation and revision, field trials and implementation. Data were collected by interview, observation, questionnaire and test. Data were analyzed using quantitative and qualitative methods to produce research products in the form of books, modules, learning plans and manuals for the use of learning applications. Product validation by experts, practicality tests carried out by users and effectiveness tests with student learning outcomes. Based on the results of data analysis, the results of this study are: 1) Research has successfully developed a project-based blended learning model in Cryptography courses. 2) The developed learning model syntax consists of 9 stages / syntax. 3) In supporting learning activities, modules, RPS and manuals are used for learning applications. All products and models developed have been developed and are categorized as valid, practical and effective.